Konstruksi Masyarakat Sadar Bencana: Pemanfaatan Kearifan Lokal dan Media Sosial - Mulyono, Joko; Paramitha, Nurina Adi; Arifiyanti, Jati; Suhartini, Elly; Ladiqi, Suyatno (The Journal of Society and Media, 2024)
The social construction process runs simultaneously. The utilization of local wisdom and social media is the result of the community construction process. Disaster-aware communities can utilize local wisdom and social media to overcome flood disasters. This research aims to analyze the construction of a disaster-aware community in Wonoasri Village, including the use of local wisdom and social media to overcome disasters. This research uses the construction theory of Berger and Luckmann. The research method used was a qualitative method with a phenomenological approach. Purpose sampling techniques were used to collect research informants. Data collection through observation, interviews, FGD, and documentation. The validity of the data using triangulation and data analysis using interactive models. The research results show that the social construction process runs simultaneously. The social construction process of the community starts from community experience, which shapes community knowledge about floods, the formation of Destana, and the transfer of knowledge, to the utilization of local wisdom and social media to overcome floods in Wonoasri Village.